Dataset on Financial Literacy, Financial Inclusion, Informal Financial Business Practices, and Intentions towards Formalization of Female Small Vendors in Lima, Peru (Research Data Journal for the Humanities and Social Sciences, 2024)
This article presents findings from a survey conducted in Lima, Peru, aimed at understanding the relationships between education, financial literacy, financial inclusion, and informal financial business practices among small female vendors. The study, which collected 118 valid responses, focused on the impact of these factors on vendors’ intentions toward formalization. Formality was assessed based on legal registration with tax authorities, emphasizing the informal practices viewed on a continuum. These practices were evaluated using a five-point gradation scale that depicted varying levels of formality. Financial literacy, financial inclusion, research data journal for the humanities and social sciences 9 (2024) and formalization intentions were measured using a five-point Likert scale, while a dichotomous question captured the formality-informality of the businesses. The demographic variables included age, gender, business tenure, employee count, and business activity. Educational level, typically treated as demographic, was considered an antecedent to financial literacy. The dataset linked to this study included raw survey data. It serves as a valuable resource for researchers, industry representatives, public authorities, and stakeholders from developing countries to deal with informality and formalization. The survey methodology and data are adaptable for use in different national contexts, facilitating comparative analysis in developing countries.